2007
DOI: 10.1167/iovs.06-1479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Riboflavin-UVA–Induced Collagen Cross-linking on Intraocular Pressure Measurement

Abstract: In this in vitro model on human corneas, CCL resulted in an overestimation of true IOP by all the tested tonometers. Although the magnitude of this effect was small, care should be taken when measuring IOP with GAT after CCL, as it results in less accurate, much more variable IOP readings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…The significance of the decrease in corneal-compensated IOP without a decrease in Goldmann-correlated IOP is a challenging issue. In an in vitro model of human corneas after CXL, Romppainen et al 19 found that all 3 tested tonometers (Goldmann applanation tonometer, dynamic contour tonometer, Tono-Pen XL) overestimated the true IOP. Wollensak et al 3 report that the IOP measured with a Goldmann tonometer did not change significantly after CXL.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the decrease in corneal-compensated IOP without a decrease in Goldmann-correlated IOP is a challenging issue. In an in vitro model of human corneas after CXL, Romppainen et al 19 found that all 3 tested tonometers (Goldmann applanation tonometer, dynamic contour tonometer, Tono-Pen XL) overestimated the true IOP. Wollensak et al 3 report that the IOP measured with a Goldmann tonometer did not change significantly after CXL.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the change in corneal biomechanics, leading to increased corneal rigidity. The difference in IOP measured following CXL ranged from 1.2 to 3.1 mm Hg, depending on the tonometer used [211,212]. …”
Section: Safetymentioning
confidence: 99%
“…Keratokonusta hastalığın ilerlemesine ve korneanın incelmesine paralel olarak 'Goldman applanasyon tonometresi için kornea kalınlığına göre hesap yapan standart nomogramların yaklaşık 2-6 mmHg' GİB 'nı düşük değerlendirdiği bildirilmiştir. 21,22 Dinamik kontür tonometre düzensiz kornealardaki biyomekanik değişikliklerden en az etkilenir. 23,24 Penetran keratoplasti sonrası gelişen ektazi / keratokonus nüksü tedavisinde gözlük ve kontakt lens kullanımından, ikinci penetran keratoplastiye kadar çeşitli yöntemler yer alır.…”
Section: Discussionunclassified